Environmental heterogeneity at small spatial scales affects population and community dynamics on intertidal rocky shores of a threatened bay system. (1st October 2018) - Dias, Gustavo M.; Christofoletti, Ronaldo A.; Kitazawa, Karina; Jenkins, Stuart R.
Abstract: Coastal areas are critical transition zones between marine and terrestrial domains that support a large diversity of species but are exposed to significant anthropogenic impacts. While most conservation and management strategies rely on understanding the drivers of diversity over large scales, the importance of small-scale variation in environmental conditions can be overlooked. Here we combined a descriptive and experimental approach to describe the spatio-temporal dynamics of sessile communities and of the population of the barnacle Chthamalus bisinuatus within Araçá Bay, a transition zone in southeastern Brazil threatened by the expansion of the São Sebastião Port. We compared the relative coverage of sessile organisms from rocky shores for 20 months and several population parameters of barnacles in three distinct regions of Araçá Bay, a few hundred meters apart: the inner portion, close to the Mãe Isabel River and the Port, the middle of the Bay, and the outer region, close to the bay entrance. Community structure varied significantly over these small spatial scales; the macroalga Ulva lactuca and the oyster Crassostrea sp. were more abundant in the inner portion of the Bay, where the influence of freshwater and organic pollution from Mãe Isabel River is more intense. Recruitment and density of C. bisinuatus was higher on the shores close to the mouth of the Bay, but individual size increased as one moves into the bay. Experimental manipulation of barnacles originally recruiting at the outer part of the bay and translocated to both outer and inner positions showed that while recruitment is restricted at the inner region, barnacle growth and survival are higher than at the outer shore. Our results suggest that the gradient of physical conditions created along the Araçá Bay can result in distinct dynamics of communities and populations and that the region close to the mouth of the bay is more dynamic, with a larger turnover of space. In the opposite direction, the inner part of the bay, which is closer to the São Sebastião Port, is more prone to be disturbed by any large human modification on the coast as populations are less dynamic and communities tend to be monopolized by species associated with organic pollution. Besides providing useful data for the management of Araçá Bay, our results also show that small-scale variation of environmental conditions can contribute to create distinct dynamics of populations and communities and should be addressed in assessments of environmental impacts on the coast. Graphical abstract: Highlights: Small spatial scale variability drives the dynamics of rocky shore populations. Barnacles are bioindicators of environmental changes. Balance between terrestrial/freshwater or marine inputs influence coastal organisms. Understanding of ecosystem functioning as support for coastal management.